Basel Core Principles and Bank Risk : Does Compliance Matter? - Demirguc-Kunt, Asli (IMF Working Papers; Working Paper ;, 2010)
This paper studies whether compliance with the Basel Core Principles for effective banking supervision (BCPs) is associated with bank soundness. Using data for over 3,000 banks in 86countries, we find that neither the overall index of BCP compliance nor its individual components are robustly associated with bank risk measured by Z-scores. We also fail to find a relationship between BCP compliance and systemic risk measured by a system-wide Zscore.